A REVIEW ON COMPREHENSIVE UNDERSTANDING OF APASTAMBHA MARMA AND ITS CLINICAL SIGNIFICANCE (International Journal of Ayurveda and Pharma Research, 2020)
The word Marma denotes the vital spots of the body. Marma Shareera is widely discussed in Ayurveda. The structural entity of these spots is not clearly explained in the classical texts so we cannot rule out the exact structural components involved. Apastambha Marma is one among 107 Marma explained in Classical textbooks. According to Sushruta, it is classified under Sira variety and it is an Urogata Kalantara Pranahara Marma. But Vagbhata has mentioned it as a type of Dhamani Marma on the basis of its structural entity. It measures about 1/2 Angula Pramana. Acharya Sushruta mentions its location as Uras, bilaterally where two Vatavaha Sira (tubular structures carrying air) are seen. Vagbhata says that it is situated in the Uras on both sides of the Parshwa. The Viddha Lakshana of this Marma as per Sushruta is Vatapoornakoshtataya, Kasa, Shwasa and Marana. However, there is a difference of opinion with Vagbhata; he has explained Raktena Poornakoshta instead of Vatapoornakoshtataya. Result: The marked area for the Apastambha Marma is at the level of 3rd costal cartilage on both the sides of the chest just lateral to the midline. As the measurement in Angula (1 cm) is not apparent so it is taken as the lengthwise, breadth wise and depth-wise. Conclusion: The area of about 2 cm lateral to carina which is the common site of injury in the bronchus can be taken as the site of Apastambha Marma as rupture of the bronchus leads to pneumothorax and the individual will show symptoms of breathing difficulty such as Kasa, Shwasa and in severe cases it may lead to the death. This explanation holds true for the Viddha Lakshana mentioned by Sushruta. Taking Shonitapoornakoshta this into consideration, pulmonary and bronchial vessels can be taken as the structures involved in Apastambha Marma which also holds good for the explanation of structural composition as per Vagbhata also i.e., it is a Dhamani Marma. Thus, we can conclude that the two Principal Bronchus along with the pulmonary vessels and bronchial vessels should be considered as the site of Apastambha Marma.